2009
DOI: 10.1371/journal.pone.0008101
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Involvement in Neuroplastic Changes Following Focal Brain Ischemia in Rats

Abstract: The pathogenesis of ischemic stroke is a complex sequence of events including inflammatory reaction, for which the microglia appears to be a major cellular contributor. However, whether post-ischemic activation of microglial cells has beneficial or detrimental effects remains to be elucidated, in particular on long term brain plasticity events. The objective of our study was to determine, through modulation of post-stroke inflammatory response, to what extent microglial cells are involved in some specific even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 77 publications
5
97
0
4
Order By: Relevance
“…PARP-1 was inhibited to dampen the microglial response to hypoxia-ischemia, but it resulted in a dampened response of BDNF in the infarct zone. They also showed decreased expression of the intracellular neuronal growth protein GAP-43 and synaptophysin, an integral membrane protein of synaptic vesicles and a marker of Articles synaptogenesis (31). Similarly, the increased microglia in our model may be a source for neurotrophic factors.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…PARP-1 was inhibited to dampen the microglial response to hypoxia-ischemia, but it resulted in a dampened response of BDNF in the infarct zone. They also showed decreased expression of the intracellular neuronal growth protein GAP-43 and synaptophysin, an integral membrane protein of synaptic vesicles and a marker of Articles synaptogenesis (31). Similarly, the increased microglia in our model may be a source for neurotrophic factors.…”
Section: Discussionmentioning
confidence: 52%
“…In an ischemic stroke rat model, Madinier et al demonstrated that decreased microglial activation was associated with decreased tissue brain derived neurotrophic factor (BDNF) expression (31). PARP-1 was inhibited to dampen the microglial response to hypoxia-ischemia, but it resulted in a dampened response of BDNF in the infarct zone.…”
Section: Discussionmentioning
confidence: 99%
“…Both basic fibroblast growth factor (bFGF) and brain derived neurotrophic factor (BDNF) are known to be upregulated in distal astrocytes and neurons between 1 and 3 days post-stroke (Lippoldt et al, 1993;Madinier et al, 2009;Speliotes et al, 1996;Wei et al, 2000). Increased neurotrophic factor expression is thought to promote dendritic and axonal sprouting in residual cortical tissue in order to support compensatory recovery.…”
Section: Molecular Changesmentioning
confidence: 99%
“…Available studies support increased BDNF production after stroke as suggested by increased BDNF levels in areas collected either at the lesion site or around the lesion for at least one week following stroke (Kokaia et al, 1998;Madinier et al, 2009;Sulejczak et al, 2007). Because increased levels of BDNF mRNA were observed in degenerating and surviving neurons in the acute post-stroke period (Comelli et al, 1992;Kokaia et al, 1995;Rickhag et al, 2007;Zhao et al, 2000), it has been generally accepted that neurons are the predominant source of neosynthesized BDNF in the ischemic brain.…”
Section: Introductionmentioning
confidence: 96%
“…Interventions that improve recovery of function are most often associated with increased BDNF levels in perilesional areas (Chen et al, 2005b;Kim et al, 2005;Vaynman et al, 2004). Conversely, attenuating BDNF levels or its effects following cerebral ischemia reduces neuroplastic changes or recovery of function either spontaneous or induced by rehabilitation (Chen et al, 2005a;Madinier et al, 2009;Ploughman et al, 2009). From these data, pharmacological strategies aimed at increasing post-ischemic cerebral BDNF production appear to be a promising option in the treatment of stroke.…”
Section: Introductionmentioning
confidence: 99%